Effect of Bi and Ti additions on the phase formation of Bi4Ti3O12 using fuel-free combustion method - Al-Amani, Umar (2009)
Bi4Ti3O12was synthesized by fuel-free combustion method using Bi(NO3)3.5H2O and Ti[OCH (CH3)2]4 and subsequent calcination. The effect of processing parameters such as Bi addition and Ti addition on the phase formation of Bi4Ti3O12was investigated. X-Ray Diffraction analysis was used to determine the formation of Bi4Ti3O12. Pure Bi4Ti3O12 powder was successfully formed with Ti addition after calcination at 800oC for 3 h. The average crystallite sizes produced were 77.9 nm, 63.6 nm and 51.8 nm with mol ratio of 4:3.1, 4:3.4 and 4:3.6, respectively. The results obtained infer that the relative amount of Ti was identified as limiting reagent in the combustion reaction and was also considered as key factor to achieve single-phase Bi4Ti3O12